The effects of psyching-up on maximal force production: A systematic review - Cusimano, K.; Freeman, P.; Pawaar, J.; Moran, J. (Strength and Conditioning Journal, 2024)
A comprehensive examination of psyching-up strategies before maximal force production is imperative to examine the efficacy of psyching-up, identify beneficial strategies for practitioners, and direct future investigations. The aim of this systematic review was to examine the efficacy of psyching-up strategies on maximal force production. The systematic review followed PRISMA guidelines. A systematic search was conducted in SPORTDiscus, PsychINFO, PsychARTICLES, MEDLINE, Google Scholar, and Web of Science. Studies were included if they used an experimental design, sampled adults, the independent variable included a psyching-up strategy that matched the working definition, and measured maximal force production measure. Twenty-seven independent studies met the inclusion criteria for this review. Collectively, 65% of the trials found that psyching-up facilitates maximal force production. Free-choice psyching-up, motivational self-talk, PETTLEP imagery, and prescribed preparatory arousal consistently enhanced performance. There was also evidence that disparity in the results may be because of the competitive experience of the participants and the type of control condition. The findings suggest that free-choice psyching-up, motivational self-talk, PETTLEP imagery, and prescribed preparatory arousal may enhance maximal force production. Future research should recruit experienced athletes to identify and test the efficacy of strategies used by applied practitioners.